Forensic Linguistics: Speech Acts of Defamation on Social Media - Fernando, Edo; Setiawan, Teguh (PT FORMOSA CENDEKIA GLOBAL, 2024)
Basically, language has been integrated with human life which is used to convey ideas, thoughts, hopes and desires to achieve various interests and functions of each. Linguists also use linguistics as a tool that can help in handling legal cases. The science of language is commonly known as forensic linguistics. Cases that are currently often sticking out are caused by the existence of social media which is used as a means of conveying the contents of the head or a form of self-expression and feelings in the public domain. In this study, an identification of speech acts of defamation in social media will be conducted. This study aims to describe speech acts in defamation cases so as not to have an impact on legal cases. The approaches taken in this study are theoretical and practical. The theoretical approach used is forensic linguistics with the tool of pragmatic analysis study in the form of speech acts. Meanwhile, the practical approach used is in the form of methodological use, namely descriptive qualitative. The analysis of lexical semantics conducted in a forensic linguistic study to prove defamation cases shows that there are data with negative and demeaning meanings; the analysis of grammatical semantics proves that semantics which studies the meaning of phrases, clauses, and sentences, there are data with negative and demeaning meanings. The pragmatic approach shows that expressive elevation speech acts show disappointment